PENGARUH UKURAN PERUSAHAAN, RISIKO BISNIS, PERPUTARAN MODAL KERJA DAN PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012 - 2014 - Elisa Agustina, 12.05.52.0176; Susilowati, Yeye (Students Journal of Accounting and Banking, 2016)
This study aimed to analyzet the influence size of the company, business risk, working capital turnover and profitability toward capital structure of Manufacturing Companies listed ont he Indonesia Stock Exchange. The populationin this studyare 180 companies listed inIndonesia Stock Exchange in 2012-2014. The sample selectionis doneby purposive sampling method. Mechanical testing of the data is by using multiple linear regression analysis. The results of analysis shows that variable business risk of the company significant positive effect on capital structure, while the size of the company and profitability variables does not effect the capital structure in Manufacturing Companieslisted onthe Indonesia Stock Exchange.Keywords: Capital Structure, Size Of The Company, Business Risk, Working Capital Turnover, Profitability